ANALYSIS OF THE NEED FOR INTERACTIVE FLIPBOOK-BASED MEDIA TO ENHANCE LEARNING INTEREST AMONG GRADE XI STUDENTS IN THE ENTREPRENEURSHIP SUBJECT AT SMK SIRAJUL FALAH PARUNG BOGOR - Khalidah, Fitria; Naura Maulidia; Rusmaini (International Journal of Economics Education Research (IJEER), 2025)
This article discusses the need for interactive media based on Flipbook in an effort to increase the interest of class XI students in entrepreneurship subjects at SMK Sirajul Falah Parung Bogor. The research methodology used is a qualitative approach and literature review. Data collection techniques in this study were through observation and interviews. The purpose of this study is to analyze students’ learning needs through interactive learning media based on flipbook in an effort to increase students’ interest in learning. This article recommends teachers to use interactive media based on flipbook for the learning process. This article is used as an additional reference or basis for further research related to the development or applicaton of digital media, especially in entrepreneurship learning at the Vocational High School level, especially at SMK Sirajul Falah Parung Bogor.